Crosslinked hydroxyl‐conductive copolymer/silica composite membranes based on addition‐type polynorbornene for alkaline anion exchange membrane fuel cell applications. Issue 1 (7th February 2017) - He, Xiaohui; Jiang, Xiong; Wang, Zijie; Deng, Yingjiao; Han, Zhilong; Yang, Yingping; Chen, Defu
Abstract : Crosslinked hydroxyl‐conductive copolymer/silica composite membranes based on addition‐type polynorbornene, poly(dodoxymethylene norbornene‐co‐norbornene‐3‐(trimethylpropyl ammonium)‐functionalized silica (QP(DNB/NB‐SiO2 ), were prepared by a sol–gel method. Copolymer composite membranes with different degree of quaternary ammonium functional silica, designated as QP(DNB/NB‐SiO2 ‐X) ( X = 5, 10, 15 and 25 wt%, respectively), displayed good dimensional stabilities with low in‐plane swelling rate of 1.32–3.7%, good mechanical properties with high elastic modulus of 605.4–756.8 MPa and high tensile strength of 13.2–20 Mpa. The achieved copolymer composite membranes could self‐assemble into a microphase‐separated morphology with randomly oriented long‐range aliphatic chain/cylinder ionic channels that were imbedded in the hydrophobic PNB matrix. Among these membranes, the QP(DNB/NB‐SiO2 ‐25) showed the parameter with ionic conductivity of 9.33 × 10 −3 S cm −1, methanol permeability of 2.89 × 10 −7 cm 2 s −1, and ion‐exchange capacity(IEC) of 1.19 × 10 −3 mol g −1 . A current density of 82.3mA cm −2, the open circuit voltage of 0.65 V and a peek power density of 32 mW cm −2 were obtained. POLYM. ENG. SCI., 58:13–21, 2018. © 2017 Society of Plastics Engineers